Dampak Pengoperasian Bus Rapid Transit (BRT) Trans Semarang Koridor VI Terhadap Pelaku Usaha Angkutan Umum di Kota Semarang - Issha Oddie Tatontos; Turtiantoro .; Laila Alfirdaus (Journal of Politic and Government Studies, 2018)
Transportation service described as the utility that support all of the society’s activity. Nearly all of the human life in the society cannot be separated from transportation. Transportation can create and increase the accessibility rate. Therefore, transportation has a close relationship with the fulfillment of human needs in performing their daily activities. For the society, especially the citizen of Semarang City, the need of public transportation is important to conduct a movement or mobility in performing the daily activities, considering that Semarang City is not only the Capital of Central Java but also the economic central of Central Java. Issue raised in this study is: How is the impact of Bus Rapid Transit (BRT) at the 4th corridor of Trans Semarang towards the business of public transportation called “Angkut” in Semarang City.Thus, the purpose of this study is to find out the impact on the operation of BRT at the 4th corridor of Trans Semarang towards the business of public transportation “Angkut” in Semarang City.Method used in this study is qualitative method with data collection techniques such as interview, observation, and documentation. There are informants in this research who are the leader of BLU UPTD of Trans Semarang, the driver of the public transportation “Angkut”, the business owner of the public transportation “Angkut”, and the user of the public transportation service on the designated route for public trasportation “Angkut”.In this research, the writer finds that 1) there are the impact on the operation of BRT at the 4th corridor of Trans Semarang towards the economy of the public transportation’s owner evidenced by the reduction of the public transportation passenger especially “Angkut” in Semarang City. 2) Both the hospitaliy and the facility offered by BRT Trans Semarang is more better than any others public transportation in Semarang City. 3) Lack of active role from angkut owner to take part in the operation of BRT Trans Semarang. From the findings above, the writer suggests to the government that in the formation of the public policy requires the participation, great coordination and great solutions from the owner of public transportation.Keywords: Public Policy, Transportation, BRT, Angkut, Impact